Desidrogenação do ácido fórmico para produção de H2: desenvolvimento de catalisadores heterogêneos - Grasser, Giovanna de Amorim (Universidade Federal de São Carlos, 2024)
The study addresses the dehydrogenation of formic acid as a sustainable alternative for hydrogen production, emphasizing the development of heterogeneous catalysts. The growing interest in hydrogen as an energy carrier, combined with the need to reduce greenhouse gas emissions, positions formic acid as a promising liquid organic hydrogen carrier (LOHC). With high energy storage potential and low toxicity, its selective dehydrogenation, generating H₂ and CO₂, is essential for applications in clean energy systems. The study highlights advancements in heterogeneous catalysis, exploring mono- and multimetallic catalysts, as well as supports and additives that enhance efficiency and stability. Catalysts based on Pd, metal alloys, and the use of supports and amine bases are shown to be strategic, especially when combined with approaches that reduce costs and improve catalytic performance. Finally, the understanding of reaction mechanisms and the integration of sustainable materials point to viable solutions aligned with the global energy transition
Dehydrogenation of formic acid for H2 production: development of heterogeneous catalysts
Keywords: Desidrogenação; Ácido fórmico; Catalisadores heterogêneos; Dehydrogenation; Formic Acid; Heterogeneous catalysts; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA